Immune Evasion Strategies during Chronic Hepatitis B and C Virus Infection - Ana Maria Ortega-Prieto; Marcus Dorner (Vaccines, 2017)
Both hepatitis B virus (HBV) and hepatitis C virus (HCV) infections are a major global healthcare problem with more than 240 million and 70 million infected, respectively. Both viruses persist within the liver and result in progressive liver disease, resulting in liver fibrosis, cirrhosis and hepatocellular carcinoma. Strikingly, this pathogenesis is largely driven by immune responses, unable to clear an established infection, rather than by the viral pathogens themselves. Even though disease progression is very similar in both infections, HBV and HCV have evolved distinct mechanisms, by which they ensure persistence within the host. Whereas HCV utilizes a cloak-and-dagger approach, disguising itself as a lipid-like particle and immediately crippling essential pattern-recognition pathways, HBV has long been considered a “stealth” virus, due to the complete absence of innate immune responses during infection. Recent developments and access to improved model systems, however, revealed that even though it is among the smallest human-tropic viruses, HBV may, in addition to evading host responses, employ subtle immune evasion mechanisms directed at ensuring viral persistence in the absence of host responses. In this review, we compare the different strategies of both viruses to ensure viral persistence by actively interfering with viral recognition and innate immune responses.